Testing the convergent and discriminant validity of the Systemic Therapy Inventory of Change Initial scales. (3rd September 2018) - Zinbarg, Richard E.; Pinsof, William; Quirk, Kelley; Kendall, Ashley; Goldsmith, Jacob; Hardy, Nathan; He, Yaliu; Sabey, Allen; Latta, Tara
Abstract: Objective: The Systemic Therapy Inventory of Change (STIC ® ) is the first multi-systemic and multi-dimensional measurement and feedback system designed for assessment in family, couple, and individual functioning. Patients fill out the STIC Initial before the first session to identify treatment targets and provide starting values for subsequent assessments of trajectories of change. This study tested the construct validity of five of the six STIC Initial scales. Methods: We administered both the STIC Initial and a set of validity measures to a relatively large sample of patients. Convergent and discriminant validity were tested using both an examination of observed correlations and confirmatory factor analysis (CFA). Results: The correlations among the observed measures showed that the convergent validity coefficients were generally large, whereas the discriminant validity coefficients were moderate to small. Similarly, CFAs suggested that the STIC total scales and subscales are good indicators of the factors they were intended to measure and that the STIC total scales and subscales are weakly related to the factors they were intended to not measure. Conclusion: The results supported the convergent and discriminant validity of the five scales of the STIC Initial. Clinical or methodological significance of this article: The clinical significance of this article is that it demonstrates that the STIC Initial should be useful for identifying treatment targets including both which systems, in addition to the facets within each system, that require targeting. The methodological significance is twofold. First, the use of CFA for testing convergent and discriminant validity is still relatively rare. Second, we demonstrated how to use CFA for a more stringent test of discriminant validity compared with the original approach described by Cole (1987 ).